2021
DOI: 10.1111/vsu.13652
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo comparison of leak testing of canine jejunal enterotomies: Saline infusion versus air insufflation

Abstract: Objective: To compare the ability to detect leakage of enterotomy closures by intraluminal injection of saline or air.Study Design: Ex vivo study. Animals: Grossly normal jejunal segments (n = 60) from five fresh canine cadavers. Methods: Eight-centimeter jejunal segments were randomly assigned to two control (saline control [n = 5], air control [5]) and two treatment groups (injection of saline [n = 25] or air [25] after enterotomies were closed in a simple continuous pattern using 4-0 glycomer 631). Initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…A major limitation of ex vivo studies is relevance of findings to live tissue, 24 as demonstrated by increased anastomotic index ex vivo versus in vivo for the mod‐IL (Figure 5). This difference could be attributed to greater tone and thickness in the live muscle layers that might have resisted expansion from stay sutures, or changes to regional blood flow and inflammation from handling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A major limitation of ex vivo studies is relevance of findings to live tissue, 24 as demonstrated by increased anastomotic index ex vivo versus in vivo for the mod‐IL (Figure 5). This difference could be attributed to greater tone and thickness in the live muscle layers that might have resisted expansion from stay sutures, or changes to regional blood flow and inflammation from handling.…”
Section: Discussionmentioning
confidence: 99%
“…Two control segments and two of each anastomosis were collected for duplicate BP recordings from each horse. The anastomoses were completed by ESC, rinsed with water, placed in a refrigerator (4°C), and then each was selected randomly for testing in a plastic tub filled with water 2,23,24 . One jejunal end was ligated with ¼‐inch umbilical tape.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Supplemental techniques shown to increase ILP such as wrapping the FEESA in omentum, serosal patch supplementation, use of surgical sealants or buttressing materials were not evaluated. 21,32 Intraoperatively, leak testing is routinely performed following FEESA using saline 7,16 or air 36 to detect gaps along the anastomotic line where supplemental sutures may be added at the discretion of the primary surgeon. This was not performed, however, which may have led to additional sutures being placed thus affecting ILP and MLP or sites of observed leakage.…”
Section: Sics Tcs Sccsmentioning
confidence: 99%